Gonadoliberin – Synthesis, Secretion, Molecular Mechanisms and Targets of Action - A. O. Shpakov; K. V. Derkach (Acta Biomedica Scientifica, 2019)
Decapeptide gonadoliberin (GnRH) is the most important regulator of the hypothalamic-pituitary-gonadal (HPG) axis that controls the synthesis and secretion of the luteinizing and follicle-stimulating hormones by gonadotrophs in the adenohypophysis. GnRH is produced by the specialized hypothalamic neurons using the site-specific proteolysis of the precursor protein and is secreted into the portal pituitary system, where it binds to the specific receptors. These receptors belong to the family of G protein-coupled receptors, and they are located on the surface of gonadotrophs and mediate the regulatory effects of GnRH on the gonadotropins production. The result of GnRH binding to them is the activation of phospholipase C and the calcium-dependent pathways, the stimulation of different forms of mitogen-activated protein kinases, as well as the activation of the enzyme adenylyl cyclase and the triggering of cAMP-dependent signaling pathways in the gonadotrophs. The gonadotropins, kisspeptin, sex steroid hormones, insulin, melatonin and a number of transcription factors have an important role in the regulation of GnRH1 gene expression, which encodes the GnRH precursor, as well as the synthesis and secretion of GnRH. The functional activity of GnRH-producing neurons depends on their migration to the hypothalamic region at the early stages of ontogenesis, which is controlled by anosmin, ephrins, and lactosamine-rich surface glycoconjugate. Dysregulation of the migration of GnRH-producing neurons and the impaired production and secretion of GnRH, lead to hypogonadotropic hypogonadism and other dysfunctions of the reproductive system. This review is devoted to the current state of the problem of regulating the synthesis and secretion of GnRH, the mechanisms of migration of hypothalamic GnRH-producing neurons at the early stages of brain development, the functional activity of the GnRH-producing neurons in the adult hypothalamus and the molecular mechanisms of GnRH action on the pituitary gonadotrophs. New experimental data are analyzed, which significantly change the current understanding of the functioning of GnRH-producing neurons and the secretion of GnRH, which is very important for the development of effective approaches for correcting the functions of the HPG axis.